Impaired glucose metabolism is associated with increased thrombin generation potential in patients undergoing angioplasty and stenting - Lee, Silvia (Cardiovasc Diabetol, 2018)
BACKGROUND: As a strong platelet agonist on the one hand and key molecule in plasmatic coagulation on the other hand, thrombin connects primary and secondary hemostasis. Thrombin generation potential reflects the individual capacity to generate thrombin, and has been associated with the occurrence of thromboembolic events. In the current study, we sought to identify predictors of thrombin generation potential in patients undergoing angioplasty and stenting for atherosclerotic cardiovascular disease. METHODS: Peak thrombin generation potential and area under the curve (AUC) of thrombin generation potential were determined with a commercially available assay in 315 patients on dual antiplatelet therapy 1 day after percutaneous intervention, and in 100 healthy individuals without cardiovascular disease. RESULTS: Median (interquartile range) peak thrombin generation potential and AUC of thrombin generation potential in the study cohort (n = 315) were significantly higher than in healthy individuals (n = 100) without cardiovascular disease (peak thrombin generation potential: 445.4 nM [354.5–551.8 nM] vs. 174.5 nM [141.2–261.2 nM]; AUC of thrombin generation potential: 5262.7 nM thrombin [4806.6–5756.9 nM thrombin] vs. 3405.2 nM thrombin [3043.6–3747.3 nM thrombin]; both p < 0.001). In patients undergoing angioplasty and stenting, hemoglobin A1c (HbA1c) was the only variable that was independently associated with both, peak thrombin generation potential and AUC of thrombin generation potential (both p ≤ 0.007). In contrast, platelet count and high-sensitivity C-reactive protein were only associated with peak thrombin generation potential, and body mass index and serum creatinine were only associated with AUC of thrombin generation potential after adjustment for covariates by multivariate linear regression analyses (all p < 0.05). Patients with HbA1c ≥ 6% had significantly higher peak thrombin generation potential and AUC of thrombin generation potential than patients with HbA1c < 6% (peak thrombin generation potential: 476.9 nM [385.8–577.9 nM] vs. 423.9 nM [335.8–529.5 nM], p = 0.002; AUC of thrombin generation potential: 5371.8 nM thrombin [4903 – 5899 nM thrombin] vs. 5172.5 nM thrombin [4731.8–5664.7 nM thrombin], p = 0.01). HbA1c ≥ 6% remained independently associated with both parameters of thrombin generation potential after multivariate linear regression analyses (both p ≤ 0.02). CONCLUSIONS: Impaired glucose metabolism is associated with increased thrombin generation potential in patients undergoing angioplasty and stenting for cardiovascular disease.